Effects of Industrial Heat Treatment on the Properties of Spruce and Pine Woods - Bilgin Icel (BioResources, 2015)
The purpose of this study was to evaluate the effects of an industrial heat treatment (ThermoWood) based on changes in the strength properties, density, and color of spruce (Picea abies) and pine (Pinus sylvestris) woods. Samples were subjected to heat treatment processes at 212 °C for a duration of 120 min. The results showed that the applied process caused a 2.56 to 6.12% decrease in density. Dimensional stability was considerably improved, with ASE values of 58% and 52% for spruce and pine, respectively. The color became darker after treatment. The process caused a significant (p<0.05) reduction (8 to 42%) for all investigated mechanical properties at a specific moisture level (12%). However, the mechanical properties of wood are closely related to its moisture content, and heat-treated wood is less hygroscopic than untreated wood. It was found that, after long-term acclimatization, heat-treated samples had almost half the equilibrium moisture content of control samples. Because the changes that occurred after this heat treatment are irreversible, it is possible that ThermoWood has lower equilibrium moisture content than untreated wood. Therefore, this should be taken into account when investigating the mechanical design values of heat-treated wood.